Study of the dynamic characteristics of the food freezing process using a cryogenic immersion freezing tank - LI,Xiao-Yan (2022)
Abstract In this work, an immersion freezing system was proposed to shorten the total freezing time and improve the quality of frozen food. The thermal performance of the refrigerant liquid prepared for using in the immersion freezing system was evaluated. A three-dimensional model (3D) was developed to investigate the dynamic characteristics of food freezing process. The effects of the refrigerant liquid inlet flow rate, inlet temperature, total freezing time and freezing rate of chicken breast, velocity and temperature distribution in the immersion freezing system were investigated. In addition, the freezing rates of food using traditional air-blast freezing and the proposed immersion freezing were evaluated. The results showed that the freezing rate of food in immersion freezing was approximately 12.85 times higher than that of the traditional air-blast freezing. When the flow rate increased from 0.11 kg·s-1 to 0.63 kg·s-1, the total freezing time shortened by 36.9%. When the temperature decreased from -25 ºC to -40 ºC, the total freezing time shortened by 35.5%. However, the temperature of the refrigerant liquid should not be too low, which will lead to high viscosity of the liquid, thus resulting in increasing in the overall power consumption of the proposed system.